OPTIMIZATION OF AN INTAKE SYSTEM USING CFD NUMERICAL SIMULATION - Sedlacek, Frantisek; Skovajsa, Michal (Proceedings in Manufacturing Systems, 2016)
The paper deals with the use of CFD numerical simulations during the design and optimization of components, which are used for air distribution taking into account temperature. An intake manifold for a light racing vehicle has been chosen as a representative example. The aim of the research is to find a solution with the best possible distribution of air to the individual cylinders of the engine, whilst ensuring the quick response of the car engine. This type of analysis is very problematic because there is high speed compressible flow of air in the intake system, pressure drops and changes of temperatures. The optimization of the shape of the airbox is achieced in connection with CFD simulation (solver Siemens NX Advanced Flow) with the geometrical optimization of the generic model of the airbox. A 1D model of the engine was created to obtain the input data for CFD analysis. Values of pressures and temperatures for the individual cylinders of the engine in relation to time were subsequently generated from the 1D model. These values are used as input for the CFD analysis. The final analysis was performed as transient for several combustion cycles of the engine.